Tingkat Pengetahuan Mahasiswa Kesehatan Terhadap Peningkatan Kesehatan Ibu dan Anak - Trisma Riskia Saputri; Syfa Uminandea; Moch. Rizqilah Safiil Adzim; Herdian Fitria Widyanto Putri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
With significant indicators like the infant mortality rate (IMR) and maternal mortality rate (MMR), maternal and child health is a critical issue impacting the quality of human resources. The purpose of this study is to assess the degree of maternal and child health knowledge among health students, taking into account their strategic importance in future health and education programs. The research was conducted at the Bhakti Wiyata Institute of Health Sciences in Kediri, using the Focus Group Discussion (FGD) method with four health students as respondents. The results of the study show that students have a reasonably good understanding of MMR, Antenatal Care (ANC), postpartum visits, the importance of basic immunizations, exclusive breastfeeding, infant care, and child development. However, there are still challenges in the areas of complementary feeding, proper breastfeeding techniques, and adequate nutrition intake, which require deeper knowledge, especially regarding the selection of nutritious foods. The conclusion of this study is that students' knowledge regarding maternal and child health is generally good but needs to be improved in several areas, particularly in complementary feeding (MP-ASI), proper breastfeeding techniques, and adequate nutrition intake.